The battle of Heligoland Bight - Osborne, Eric W. (Twentieth-century battles., 2006)
"The battle of Heligoland Bight was the first major action between the British and German fleets during World War I. The British orchestrated the battle as a warning to the German high command that any attempt to operate their naval forces in the North Sea would be met by strong British resistance. Heligoland Island guarded the entrance to the main German naval anchorage at Kiel. Fought on August 28, 1914, the engagement was complicated by dense fog, the piecemeal engagement of German forces, and the unexpected appearance in the area of additional British ships, which were hard to distinguish from foe. Initial British damage was significant; however, fearing that the protracted battle would allow the bulk of the German fleet to join the battle, the British brought in their battle cruiser reinforcements and won the day, inflicting heavy losses on the Germans."--Publisher's summary